How do agricultural socialization services drive green transition of farmers’ grain production under “dual-carbon” targets: an analysis of moderating effects based on factor allocation - Wang, Jinzhi; Long, Fang (Frontiers in Environmental Science, 2025)
The green production transition represents a significant strategy for promoting organic agriculture and achieving the goal of sustainable development of grain systems. It is an important tool for resource utilization of agricultural waste and reduction of nitrogen and phosphorus emissions. Based on the survey data of grain farmers in Jiangsu Province in 2022, this paper empirically analyzes the impact and mechanism of Agricultural Socialization Services on the green transition of farmers’ grain production based on the use of the finite mixture model (FMM) to measure the degree of green transition of farmers’ grain production. The study shows that the participation of Agricultural Socialization Services is conducive to the green transition of farmers’ grain production, and the more participation of socialization services, the deeper the degree of green transition of farmers’ grain production. The mechanism test shows that socialization services promote the green transition of farmers’ grain production mainly by regulating Plot Size and Labor Transfer. The extension analysis shows that compared with ordinary farmers, Agricultural Socialization Services play a more obvious role in promoting the Green Transition of Grain Production of new type of agricultural operating entit. This study addresses a theoretical gap in the field of green production under service outsourcing. Therefore, this study is of great significance for the promotion of green development in agriculture and the realisation of the goal of “carbon peak and neutrality”.